1973
DOI: 10.1088/0029-5515/13/6/007
|View full text |Cite
|
Sign up to set email alerts
|

Short-pulse-laser-heated plasma experiments

Abstract: The interaction between time-tailored, high-intensity laser radiation and spherical light-element targets is investigated. Simultaneous measurements of the laser plasma electron temperature, charged-particle distribution, absorbed energy, neutron yields and backscattered light intensity and spectra were made. For 100 ps, wide laser pulses focused to intensities ranging between 3 × 1015 and 2 × 1016 W/cm2 on 150-200μm-diameter LiD and C36D74 targets, plasmas with electron temperatures up to 1.2 keV and target-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Recently, an effort has been made to explain the low level of backscattered radiation due to the effect of turbulence [3]. Another significant result which has emerged from the laser plasma experiments is the absence of sidescatter [2]. In this letter we suggest a physical mechanism which could be relevant to this interesting observation.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, an effort has been made to explain the low level of backscattered radiation due to the effect of turbulence [3]. Another significant result which has emerged from the laser plasma experiments is the absence of sidescatter [2]. In this letter we suggest a physical mechanism which could be relevant to this interesting observation.…”
mentioning
confidence: 76%
“…The problem of radiation backscatter from laser plasmas has received significant attention because of its relevance to laser fusion [1]. The extensive theoretical work, however, does not agree very well with the experimental findings [2]. Recently, an effort has been made to explain the low level of backscattered radiation due to the effect of turbulence [3].…”
mentioning
confidence: 99%
“…In Ref. 79, Soures et al reported over 10 4 neutrons from a one-beam laser tightly focused onto solid spherical LiD targets; based on time-of-flight measurements, these neutrons originated from the target. This same conclusion was drawn by Basov et al 80 from time-of-flight measurements in their multibeam system.…”
Section: A the Quest For Neutronsmentioning
confidence: 99%
“…As an example, definite values of the intensity of radiation in the interaction domain are difficult to settle and figures given can as a rule only be taken as estimates. Diagnostics of the laser-plasma interaction region for the pellet problem is for obvious reasons very intricate, and new diagnostic techniques are searched for, [15]. The experimental results on the reflectivity of laser produced plasmas also differ widely, Concerning the present and future laser-plasma experiments let us here only furthermore mention that the laser technology progresses along several lines including the carbon dioxide, neodynium, iodine and other types of lasers and that by 1976 lasers producing 10 kJ within 100 ps are expected to be available, [19].…”
Section: Introductionmentioning
confidence: 99%